Pengendali TV Dual Channel dan Kipas Angin Berbasis Smartphone Android - Mohamad Lukman Nurcahyana (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2015)
Abstract - This research will focus on the design of dual channel television control systems and fan speed control. The design of a dual channel TV controller system and fan speed control uses wireless media as a link between an Android smart phone, Raspberry Pi B +, TV, and fan. To design a dual channel TV controller system and control wind kipsa, it includes an Android smartphone, wi-fi module type TL-WN832N TP-Link and Raspberry pi B +. Android smartphones function as TV controllers and fans with applications installed on Android smartphones. The TP-Link TL-WN832N wi-fi module functions as a wireless multimedia link between the Raspberry Pi B + and Android smartphones. Raspberry pi B + functions like processing data sent by an Android smartphone to control the TV or fan. Thus, the system design tool can replace 2 controllers and TV fans in one device that can control the TV and fan using an Android smartphone Keyword : Android smartphone, TP-Link TL-WN832N Wi-Fi module, Raspberry Pi B +